Immunohistochemical Characterization of Sympathetic Chain Ganglia (SChG) Neurons Supplying the Porcine mammary Gland. (9th January 2015) - Franke‐Radowiecka, A.; Wąsowicz, K.; Klimczuk, M.; Podlasz, P.; Zalecki, M.; Sienkiewicz, W.
Summary: The aim of this study was to investigate the chemical coding of mammary gland‐projecting SChG neurons using double‐labelling immunohistochemistry. Earlier observation showed that after injection of the retrograde tracer fast blue (FB) into the second, right thoracic mamma, FB+ mammary gland‐projecting neurons were found in Th1‐3, Th9‐14 and L1‐4 right SChG. The greatest number of FB+ nerve cell bodies was observed in Th10 (approx. 843) and Th11 (approx. 567). Neurons projecting to the last right abdominal mamma were found in L1‐4 SChG. The greatest number of FB+ neurons was observed in L2 (approx. 1200). Immunohistochemistry revealed that the vast majority of FB+ mammary‐projecting neurons contained immunoreactivities to TH (96.97%) and/or DßH (95.92%). Many TH/DßH‐positive neurons stained for SOM (41.5%) or NPY (33.2%), and less numerous nerve cells expressed VIP (16.9%). This observation strongly corresponds to the results of previous studies concerning the immunohistochemical characterization of nerve fibres supplying the porcine mammary gland.